2012
DOI: 10.1002/ange.201204925
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic Spiroketal Bisphosphine Ligands: Palladium‐Catalyzed Asymmetric Allylic Amination of Racemic Morita–Baylis–Hillman Adducts

Abstract: The design of chiral ligands plays a central role in the development of chiral catalysts for asymmetric reactions, in which the right combination of a sterically well-defined scaffold with a chelating moiety can lead to excellent enantioselective control in the catalysis. [1] From this point of view, spirobackbones (Scheme 1) have been recognized as one of the privileged structures for the construction of chiral ligands [2] ever since the pioneering work by Chan et al. (SpirOP), Sasai and co-workers, and Zhou … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 71 publications
0
19
0
Order By: Relevance
“…Synthesis of chiral Ph-BINMOL-based aldehyde 2 c [10b] and corresponding phosphine ligand L6: a) [1,2]-Wittig rearrangement, [12] iBuLi, THF, À78 8C; b) TMSCl (TMS = trimethylsilyl), NaI; c) NaH, MOMCl; d) nBuLi, DMF, Et 2 O; e) HCl, THF; and f) CH 2 Cl 2 /EtOH, at room temperature. Synthesis of chiral Ph-BINMOL-based aldehyde 2 c [10b] and corresponding phosphine ligand L6: a) [1,2]-Wittig rearrangement, [12] iBuLi, THF, À78 8C; b) TMSCl (TMS = trimethylsilyl), NaI; c) NaH, MOMCl; d) nBuLi, DMF, Et 2 O; e) HCl, THF; and f) CH 2 Cl 2 /EtOH, at room temperature.…”
Section: Copper-catalyzed Conjugate Addition Of Et 2 Zn To Enonesmentioning
confidence: 99%
“…Synthesis of chiral Ph-BINMOL-based aldehyde 2 c [10b] and corresponding phosphine ligand L6: a) [1,2]-Wittig rearrangement, [12] iBuLi, THF, À78 8C; b) TMSCl (TMS = trimethylsilyl), NaI; c) NaH, MOMCl; d) nBuLi, DMF, Et 2 O; e) HCl, THF; and f) CH 2 Cl 2 /EtOH, at room temperature. Synthesis of chiral Ph-BINMOL-based aldehyde 2 c [10b] and corresponding phosphine ligand L6: a) [1,2]-Wittig rearrangement, [12] iBuLi, THF, À78 8C; b) TMSCl (TMS = trimethylsilyl), NaI; c) NaH, MOMCl; d) nBuLi, DMF, Et 2 O; e) HCl, THF; and f) CH 2 Cl 2 /EtOH, at room temperature.…”
Section: Copper-catalyzed Conjugate Addition Of Et 2 Zn To Enonesmentioning
confidence: 99%
“…Most recently, Ding [11] and Liu [12] reported the palladium-catalyzed N-allylic alkylation of MBH adducts with simple aromatic amines through a p-allylpalladium complex. Considering the strong electron-withdrawing effect of the tosyl group, we wondered whether tosylhydrazone could be utilized as a suitable nucleophile to react with MBH carbonates for the construction of optically active N-alkylated tosylhydrazones.…”
Section: Introductionmentioning
confidence: 99%
“…Having identified the best catalyst, the effect of the solvents was also tested. Among the various solvents screened, to our surprise, we found that almost all of them had a negligible effect on the enantioselectivity except for toluene (entries [11][12][13][14][15][16]. However, the regioselectivity showed a strong solvent dependence.…”
mentioning
confidence: 98%
“…[11] We envisioned that SKP/Pd-catalyzed AAA of MBH adducts with nucleophiles of b-ketocarbonyl compounds [12] might provide an excellent approach for the construction of vicinal chiral tertiary and quaternary centers.Accordingly,the reaction of the MBH adduct 1a and b-ketoester 2a was taken for aproof-of-concept prototype to survey the reaction conditions (Table 1). [11] We envisioned that SKP/Pd-catalyzed AAA of MBH adducts with nucleophiles of b-ketocarbonyl compounds [12] might provide an excellent approach for the construction of vicinal chiral tertiary and quaternary centers.Accordingly,the reaction of the MBH adduct 1a and b-ketoester 2a was taken for aproof-of-concept prototype to survey the reaction conditions (Table 1).…”
mentioning
confidence: 99%
“…[b] 3aa/4aa [c] d.r. [a] Unless otherwise noted, the reactions were performed under conditionsB.The data within parentheses are the yields of isolated 3.In each case, the b/l and d.r.values were determined by 1 Considering the bifunctional role of SKPs in the allylic substitution of MBH acetates, [11] as well as the sense of asymmetric induction in the titled reaction, as chematic representation of the stereocontrol model is proposed in Figure 1. Except for 3ap,all the products (3aaao)w ere obtained in excellent enantioselectivities (93-> 99 % ee).…”
mentioning
confidence: 99%